THE IMPACT OF HEALTH EDUCATION USING TAE’ LANGUAGE ON KNOWLEDGE AND ATTITUDES OF PREGNANT WOMEN ABOUT DANGER SIGNS OF PREGNANCY - Bestfy Anitasari; Abri Hadi; Santi (Jurnal Kesehatan, 2022)
Knowledge of the danger signs of pregnancy becomes the basis for pregnant women to determine attitudes and behavior in early detection and take immediate action if they feel the danger signs of pregnancy. This study aims to analyze the impact of Health Education using Tae Language on the knowledge and attitudes of pregnant women about the danger signs of pregnancy. The design in this research is a Quasi Experiment, one group pretest and posttest. The number of samples was 30 people who were selected by purposive sampling in accordance with the inclusion and exclusion criteria. The results showed that there was an effect of Health Education on the knowledge of mothers with p value = 0.000 <α = 0.005 as well as the influence of Health Education on the attitudes of pregnant women about the danger signs of pregnancy with p value = 0.000 <α = 0.005. Health workers are required to be more active in educating women during childbearing as a primary preventive activity in an effort to reduce maternal and infant mortality rates which are still quite high in Indonesia.